2009
DOI: 10.3413/nukmed-0221
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of adjuvant external-beam radiotherapy for differentiated thyroid cancer

Abstract: The MSDS trial showed low mortality and recurrence rates and a weak benefit of RTx in terms of local control that did however not reach statistical significance. Routine RTx in locally invasive DTC can no longer be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 24 publications
0
23
0
1
Order By: Relevance
“…The MSDS trial represents the largest multi-institutional cohort of high-risk patients with differentiated thyroid cancer patients worldwide second to the North American National Thyroid Cancer Treatment Cooperative Study (12,16,17). Inclusion criteria were PTC and FTC with extrathyroidal extension and without known distant metastases at the time of primary diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The MSDS trial represents the largest multi-institutional cohort of high-risk patients with differentiated thyroid cancer patients worldwide second to the North American National Thyroid Cancer Treatment Cooperative Study (12,16,17). Inclusion criteria were PTC and FTC with extrathyroidal extension and without known distant metastases at the time of primary diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…and 70 years (excl.) at the time of initial surgery, completion of primary surgical therapy with R0-or R1-resection, Karnofsky index R70% and freedom from distant metastases at the time of initial radioiodine therapy (10)(11)(12). Exclusion criteria were poorly differentiated (insular) thyroid carcinoma, secondary cancer and R2-resection with macroscopic tumour residues.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…A single randomized prospective trial in Germany failed to recruit adequate patients and only 26 received EBRT. 1 However, a mounting number of retrospective studies have been reported, including several recent studies showing significant benefit for EBRT in select patients. 24 The Endocrine Surgery Committee of the American Head and Neck Society (AHNS) here provides recommendations regarding the use of EBRT for locoregional control in DTC, based on review of the literature and expert opinion of the authors.…”
Section: Introductionmentioning
confidence: 99%
“…No prospective trials have been performed, and a recent German study designed to address this issue was closed because only 45 of 311 patients recruited agreed to randomization (60).…”
Section: Adjuvant Therapiesmentioning
confidence: 99%